Characterization of the microbial community in a biotrickling filter treating a complex mixture of gaseous compounds causing odor nuisance. Issue 6 (1st March 2021) - Aguirre, Alberto; Gentina, Juan C; Malhautier, Luc; Fanlo, Jean‐Louis; Vergara‐Fernandez, Alberto; Scott, Felipe; Aroca, Germán
Abstract: BACKGROUND: Industrial gaseous emissions causing odor nuisance has become a major environmental issue in many countries. Biotrickling filters are suitable for treating mixtures of gaseous compounds with high removal efficiencies. The aim of this work was to determine the vertical distribution of microbial communities established in a biotrickling filter treating a mixture of gaseous compounds causing odor nuisance, and to correlate its performance with the spatial and temporal distribution of inoculated bacteria. RESULTS: In the long‐term operation, at day 538, the removal efficiencies were 100% for ammonia and H2 S, 73% for methanol, 63% for trimethylamine, 41% for dimethylsulphide, and 32% for 2, 5‐dimethylpirazyne; the elimination capacities were 1.5 [g NH3 m −3 bed h −1 ], 0.7 [g H2 S m −3 bed h −1 ], 0.7 [g MeOH m −3 bed h −1 ], 3.3 [g TMA m −3 bed h −1 ], 0.21 [g DMS m −3 bed h −1 ], and 0.6 [g 2, 5‐DMP m −3 bed h −1 ]. A stratification pattern of pollutants degradation along the biotrickling filter (BTF) was identified, where most of the removal of NH3, TMA, and H2 S occurred at the lower level of the column, the removal of methanol and 2, 5‐dimethylpyrazine occurred at low and medium levels, and the removal of dimethylsulphide occurred mainly at the upper levels. High‐throughput DNA sequencing analysis showed a colonization by bacteria genera different from the inoculated and a stratification of these bacteria along the BTF. CONCLUSION: There is stratification in the biofilm of a biotrickling filter during its long‐term operation, and a relationship between the stratification of the microbial communities and the removal of the complex mixture of gases was identified. © 2021 Society of Chemical Industry